Corporate Social Responsibility and Financial Performance in Europe: The Moderating Effects of Industry, Culture, and Governance - Fatmy, Veda; Haavisto, Venla; Äijö, Janne (John Wiley & Sons, 2025)
This paper investigates the relationship between corporate social responsibility (CSR) and financial performance for European firms, and the moderating roles of industry and country-specific factors in this relationship. Studying a sample of 2340 companies across 18 countries, we find Environmental, Social and Governance (ESG) scores to positively and significantly relate to both profitability and firm value, and that this relationship is significantly moderated by industry ESG sensitivity. Additionally, we show that firms in culturally CSR-rewarding countries have a significantly stronger relationship between their social and financial performance. We also find that country-level shareholder orientation positively moderates the relationship between CSR and firm performance, which is largely driven by the effects of good corporate governance on profitability and firm value. Overall, our findings suggest that policymakers need to account for country and industry-level effects to effectively improve the link between corporate sustainability and performance.
Keywords: corporate social responsibility; country culture; financial performance; industry; shareholder protections; Finance; Rahoitus; Finance; Rahoitus